Biogenic Silver Nanoparticles Strategically Combined With Origanum vulgare Derivatives: Antibacterial Mechanism of Action and Effect on Multidrug-Resistant Strains - Scandorieiro, Sara; Rodrigues, Bianca C. D.; Nishio, Erick K.; Panagio, Luciano A.; de Oliveira, Admilton G.; Durán, Nelson; Nakazato, Gerson; Kobayashi, Renata K. T. (Frontiers in Microbiology, 2022)
Multidrug-resistant bacteria have become a public health problem worldwide, reducing treatment options against several pathogens. If we do not act against this problem, it is estimated by 2050 that superbugs will kill more than current COVID-19 pandemic. Among solutions to combat antibacterial resistance, there is increasing demand for new antimicrobials. Antibacterial activity of binary-combinations, containing bioAgNP (biogenically synthesized silver nanoparticles using Fusarium oxysporum), oregano essential oil (OEO), carvacrol (Car), and thymol (Thy), were evaluated: OEO plus bioAgNP, Car plus bioAgNP, Thy plus bioAgNP, and Car plus Thy. This study shows that mechanism of action of Thy, bioAgNP, and Thy plus bioAgNP involves damage in membrane and cell wall (surface blebbing and disruption seen by electron microscope), causing cytoplasmic molecules leakage (ATP, DNA, RNA, and total proteins), and oxidative stress by enhancing intracellular reactive oxygen species and lipid peroxidation; similar mechanism happens for OEO and Car, except oxidative stress. Combination containing bioAgNP and oregano derivatives, especially thymol, shows strategic antibacterial mechanism; thymol disturbs selective permeability of cell membrane and consequently facilitates the access of nanoparticles to bacterial cytoplasm. BioAgNP-treated Escherichia coli developed resistance to nanosilver after 12 days of daily exposition; Thy plus bioAgNP combination prevented emergence of resistance to both antimicrobials, so mixture of antimicrobials is a strategy to extend their life. For antimicrobials alone, minimal bactericidal concentration ranges were 0.30 – 2.38 mg/mL (OEO), 0.31 – 1.22 mg/mL (Car), 0.25 – 1 mg/mL (Thy), and 15.75 – 31.5 µg/mL (bioAgNP). Time-kill assays showed that oregano derivatives acted very fast (at least 10 s), while bioAgNP took at least 30 min to kill Gram-negative bacteria and 7 h to kill methicillin-resistant Staphylococcus aureus (MRSA). All combinations resulted in additive antibacterial effect, reducing significantly minimal inhibitory concentration and acting faster than bioAgNP alone; they also showed no cytotoxicity. This study describes for the first time the effect of Car and Thy combined with bioAgNP (produced with F. oxysporum components) against bacteria for which efficient antimicrobials are urgently needed, such as carbapenem-resistant strains (E. coli, Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa) and MRSA.